Burn bright : a holistic self-care guide to being present, fulfilled, and happy - Rymsha, Charlene (Live well, 2021)
"Do you have trouble getting started at work? Do you feel depleted of energy and not productive? Do you have a hard time concentrating or do not feel satisfied from your achievements? If so, you may be experiencing burnout. In Burn Bright, burnout expert Charlene Rymsha teaches her proven and holistic approach to efficiently and effectively getting unstuck and provides the tools and support to maintain lasting-and evolving-transformation from the empty feeling caused by burnout. Powerful and reflective meditations coupled with positive reinforcement strategies will get you burning brightly in no time!"--